Incidental renal tumours on low-dose CT lung cancer screening exams. (June 2017) - Pinsky, Paul F; Dunn, Barbara; Gierada, David; Nath, P Hrudaya; Munden, Reginald; Berland, Lincoln; Kramer, Barnett S
Introduction: Renal cancer incidence has increased markedly in the United States in recent decades, largely due to incidentally detected tumours from computed tomography imaging. Here, we analyze the potential for low-dose computed tomography lung cancer screening to detect renal cancer. Methods: The National Lung Screening Trial randomized subjects to three annual screens with either low-dose computed tomography or chest X-ray. Eligibility criteria included 30 + pack-years, current smoking or quit within 15 years, and age 55–74. Subjects were followed for seven years. Low-dose computed tomography screening forms collected information on lung cancer and non-lung cancer abnormalities, including abnormalities below the diaphragm. A reader study was performed on a sample of National Lung Screening Trial low-dose computed tomography images assessing presence of abnormalities below the diaphragms and abnormalities suspicious for renal cancer. Results: There were 26, 722 and 26, 732 subjects enrolled in the low-dose computed tomography and chest X-ray arms, respectively, and there were 104 and 85 renal cancer cases diagnosed, respectively (relative risk = 1.22, 95% CI: 0.9–1.5). From 75, 126 low-dose computed tomography screens, there were 46 renal cancer diagnoses within one year. Abnormalities below the diaphragm rates were 39.1% in screens with renal cancer versus 4.1% in screens without (P < 0.001). Cases with abnormalities below the diaphragms had shorter median time to diagnosis than those without (71 vs. 160 days, P = 0.004). In the reader study, 64% of renal cancer cases versus 13% of non-cases had abnormalities below the diaphragms; 55% of cases and 0.8% of non-cases had a finding suspicious for renal cancer (P < 0.001). Conclusion: Low-dose computed tomography screens can potentially detect renal cancers. The benefits to harms tradeoff of incidental detection of renal tumours on low-dose computed tomography is unknown.